Does the International Narcotics Control Board (INCB) sufficiently prioritise enablement of access to therapeutic opioids? A systematic critical analysis of six INCB annual reports, 1968-2018 - Joseph D Clark; Miriam Johnson; Blessing Fabowale; Michael Farrelly; David Currow (Inishmore Laser Scientific Publishing Ltd, 2020)
**Background** The International Narcotics Control Board (INCB) has overseen international drug control since 1968 with the dual remit of restricting illicit production and use of controlled substances, whilst enabling access for clinical purposes. Two opioid crises are present under its jurisdiction: i) abuse, dependence and premature mortality in high-income countries; and ii) inadequate supply of opioids for clinical purposes for most of the world represented almost exclusively by low- and middle-income countries. **Methods** Systematic critical analysis using corpus linguistics as a method of document analysis to investigate the regulatory climate promoted by the INCB, through language used regarding opioids in a representative sample of annual Reports, 1968-2018. Instances of key terms (narcotics, opiates, opioids, analgesia) were retrieved, with surrounding text for context. Two systematic coding phases were undertaken by two researchers, adjudicated by a third, to develop themes. We report frequencies per-1000 words of themes and key terms, aggregated and by decade. **Results** Five themes were developed within three domains: abuse and dependency, illegal trade (domain 1: illicit uses); policy, enforcement and context (domain 2: illicit and therapeutic uses), and access for therapeutic use, estimates of need (domain 3: therapeutic uses). For fifty years, the INCB has focussed predominantly upon domain 1: illicit uses, with little attention to domain 3: therapeutic Uses. Decreasing attention is provided to the estimates of annual requirements system, under which global opioid access to opioids is documented as inadequate. **Conclusions** The INCB must consider how improving availability of therapeutic opioids could reduce widespread suffering safely and effectively. Urgent international and national action is required to improve methods of accurately estimating population-level needs for opioids for all therapeutic requirements. Fears of illicit production or use should not limit the prospects of accessing appropriate therapeutic opioids where the majority of the world, today, have no realistic access.